Sistem Pendidikan Karakter Sosial Santri Ditinjau dari Perspektif Perilaku Manusia dalam Organisasi : Studi kasus di Pondok Pesantren Al-Qohhariyyah Desa Sukatani Kecamatan Pacet - Dede Setiawan; Kun Nurachadijat (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
This study investigates the Social Character Education System at Pondok Pesantren Al-Qohhariyyah in Pacet, Cianjur Regency. The research method employed is qualitative descriptive, involving key informants such as the head of Madrasah Aliyah, the council of teachers, the head of the male boarding school, administrators, and students. Data was gathered through observation, interviews, and document analysis, utilizing triangulation. Findings indicate that the pesantren combines tradition and modern approaches in social character education. There are two main models: the Salafi pesantren, which maintains the teaching of classical texts, and the Khalafi pesantren, which incorporates general education into the madrasah curriculum. Character education is delivered through various methods like sorogan, wetonan, bandongan, and mudzakarah. Majelis ta'lim also engages the local community in religious education. This system positively impacts the formation of students' social character by integrating traditional and modern values, creating a dynamic and creative learning environment.